1992
DOI: 10.1139/z92-026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an experimental wolf reduction on beaver in Papineau-Labelle Reserve, Quebec

Abstract: From 1983 to 1988 the densities of beaver colonies in traplines from within two blocks were compared. The first block (RB, 275 km2) was included in a larger area where wolves were reduced almost 60% over three winters. The second block (UB, 265 km2) received no wolf-control treatment. Beaver trapping, formerly prohibited, was allowed in 1984 in 5 of 11 trapline units of RB and 5 of 9 units of UB after the first wolf reduction. The density of colonies (0.8/km2) remained stable in UB, even where beaver trapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Wolves in some areas in North America helped to decrease beaver colonies (Potvin et al 1992), provided that both wolf and beaver populations reached high levels (Shelton and Peterson 1983). In Latvia, wolves seemed to have little effect on the increasing numbers of beavers.…”
Section: Discussionmentioning
confidence: 99%
“…Wolves in some areas in North America helped to decrease beaver colonies (Potvin et al 1992), provided that both wolf and beaver populations reached high levels (Shelton and Peterson 1983). In Latvia, wolves seemed to have little effect on the increasing numbers of beavers.…”
Section: Discussionmentioning
confidence: 99%
“…In boreal situations, such as the CCGP, a lessening of foraging time means reduced exposure to Gray Wolves. Potvin et al (1992) demonstrated that Gray Wolves are highly effective predators. In subsequent studies, Basey and Jenkins (1995) further showed that Beavers actually trade off maximum profitability against minimization of Wolf predation.…”
mentioning
confidence: 99%
“…We hypothesized that wolf density would decrease and that deer numbers and density, the buck harvest, and fawn survival would all increase as a result of wolf control. The effects on beaver are presented elsewhere (Potvin et al 1992). …”
Section: Introductionmentioning
confidence: 99%